2009
DOI: 10.1063/1.3207828
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond-pulse fiber lasers mode-locked with nanotubes

Abstract: We demonstrate that mode-locking of ytterbium fiber lasers with a carbon nanotube saturable absorber can produce pulses ranging from 20 ps to 2 ns at repetition rates between 21 MHz and 177 kHz, respectively, depending on cavity length. Nonlinear polarization evolution is not responsible for mode-locking. Even in the nanosecond regime, clean single pulses are observed and the pulse train exhibits low jitter. Combined with extremely large chirp, these properties are suited for chirped-pulse amplification system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 20 publications
2
92
0
Order By: Relevance
“…The normal dispersion laser cavity provided generation of 1.5-ps chirped pulses, which could be compressed down to 250 fs outside the cavity [50]. In Kelleher et al [223], the possibility of pulse duration adjustment was demonstrated within the range from 20 ps to 2 ns at repetition rates between 21 MHz and 177 kHz. Mode-locked operation in Yb-doped fibre lasers was also demonstrated using DWNT-SA [72].…”
Section: Evanescent Field Interactionmentioning
confidence: 99%
“…The normal dispersion laser cavity provided generation of 1.5-ps chirped pulses, which could be compressed down to 250 fs outside the cavity [50]. In Kelleher et al [223], the possibility of pulse duration adjustment was demonstrated within the range from 20 ps to 2 ns at repetition rates between 21 MHz and 177 kHz. Mode-locked operation in Yb-doped fibre lasers was also demonstrated using DWNT-SA [72].…”
Section: Evanescent Field Interactionmentioning
confidence: 99%
“…The next level was achieved in the breakthrough works [5,6] in mode-lock fibre lasers with a several km cavities. Other examples of passive mode locking in fibre lasers with > 1 km resonators have been demonstrated in the subsequent works [7][8][9][10][11][12]. Such a dramatic elongation of the laser resonator led to more than two orders of magnitude increase in the output pulse energy at the same pump power.…”
mentioning
confidence: 90%
“…Mode-locked lasers based on rare-earth media and operating with a net normal dispersion map, generating so-called dissipative solitons [12,16,17], were suggested as a means of overcoming the limits on pulse energy imposed by the soliton regime. Such systems were shown to support highly linearly chirped pulses [12,16,17], with durations up to several nanoseconds [12]. Thus they can be amplified and compressed without temporal and spectral degradation due to nonlinearities.…”
mentioning
confidence: 99%
“…The square-shaped spectrum is a recognizable feature of lasers operating in the dissipative soliton regime [12]. Such systems generate pulses carrying a large and predominantly linear chirp [12], and are suitable for compression [12]. The RF trace [ Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation